Learning adaptation to climate change from past climate extremes: Evidence from recent climate extremes in Haryana, India - Aryal, Jeetendra Prakash; Jat, Mangi Lal; Sapkota, Tek Bahadur; Rahut, Dil Bahadur; Rai, Munmun; Jat, Hanuman Sahay; Sharma, Parbodh Chander; Stirling, Clare M (Emerald Publishing Limited, 2020)
Purpose Conservation agriculture-based wheat production system (CAW) can serve as an ex ante measure to minimize loss due to climate risks, especially the extreme rainfall during the wheat production season in India. This study aims to examine whether farmers learn from their past experiences of exposure to climate extremes and use the knowledge to better adapt to future climate extremes.